PENYUSUNAN LAPORAN KEUANGAN UMKM BERDASARKAN SAK EMKM: STUDI KASUS TOKO AL HUDA KEBUMEN - Luthfia, Arawindha Delphin; Suryani, Rista Ayu; Sumaryanto (Jurnal Pengabdian Indonesia (JPI), 2025)
Most micro, small, and medium enterprises (MSMEs) in Indonesia have not prepared financial statements that comply with applicable standards, posing risks to inaccurate business decisions and limiting opportunities to access funding. This study aims to assist Al Huda Plastic and Baking Supplies Store in Kebumen in preparing financial statements in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This topic was chosen due to the importance of accounting literacy in managing small businesses, as the understanding of MSME actors regarding accounting standards is still relatively low. This research uses a descriptive qualitative method with a case study approach, utilizing observation, semi-structured interviews, and documentation as data collection techniques. The results show that Al Huda Store has been recording its finances manually. However, these records do not yet cover the components of financial statements required by SAK EMKM, such as the income statement, statement of financial position, and notes to the financial statements. The preparation of financial statements based on these standards has been carried out and demonstrates more accurate and structured financial information. In conclusion, the implementation of financial statements based on SAK EMKM in MSMEs plays a very important role in increasing accountability and quality in business decision-making. The results of this study also provide practical examples that can be used as references and re-applied by other MSMEs with similar characteristics